1984
DOI: 10.4141/cjas84-073
|View full text |Cite
|
Sign up to set email alerts
|

Body Heat Storage, Metabolism and Respiration of Cows Abruptly Exposed and Acclimatized to Cold and 18 °c Environments

Abstract: . eNo Wr:rNcenor, R. 1984. Body heat storage. metabolism and respiration ofcows abruptly exposed and acclimatized to cold and iB"C environments. Can. J. Anim. Sci. 64 641-653. Six cows were alternated between cold ( -30 to 0"C) and I 8"C environments. Rectal (Tr), mean skin (Ts) and mean body

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 3 publications
(4 reference statements)
2
17
0
1
Order By: Relevance
“…The value of skin surface temperature (Ts) was calculated based on the formula Mc. Lean et al [6] could be seen in Equation 1. Based on the value of rectal temperature (Tr) and the skin surface (Ts), the value of body temperature (Tb) was calculated using the formula Mc Lean et al [6] which could be seen in Equation 2.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The value of skin surface temperature (Ts) was calculated based on the formula Mc. Lean et al [6] could be seen in Equation 1. Based on the value of rectal temperature (Tr) and the skin surface (Ts), the value of body temperature (Tb) was calculated using the formula Mc Lean et al [6] which could be seen in Equation 2.…”
Section: Methodsmentioning
confidence: 99%
“…Lean et al [6] could be seen in Equation 1. Based on the value of rectal temperature (Tr) and the skin surface (Ts), the value of body temperature (Tb) was calculated using the formula Mc Lean et al [6] which could be seen in Equation 2. Environmental conditions were monitored through the measurement of air temperature and relative humidity every hour for 5 days of study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The calorimetry system used was as described by McLean et al (1984) with the addition of a switching apparatus that allowed the system to collect and analyze samples from two calorimetry hoods at 15-min intervals. The heifers were randomly allocated to the two calorimetry hoods for RHP measurement to avoid systematic errors.…”
Section: Data Collectionmentioning
confidence: 99%
“…Environmental temperature variability may impact adaptation through induction of variability in temperature of the body core (T core ) as Bergen et al (2001) also showed that exposure of beef heifers to cold temperatures during only part of the day resulted in increased variability, but not the mean of T core . In comparison, continuous cold exposure throughout the day has been shown to reduce (Young 1975), increase the variability of (McLean et al 1984) or have no effect on T core (Lefcourt and Adams 1998). Although the physiological cues that lead to the development of acclimatization are not known, a change in T core is a possible stimulus for the development of acclimatization.…”
mentioning
confidence: 99%